Redes sociais e o processo de recuperação na Fazenda da Esperança - Moraes, Denise Pena de (2010)
Social networks are formed when relationships are established between actors over a common goal, such as building new paths for those who seek recovery and life improvement. This research is a case study that analyzes social network formation at Fazenda da Esperança (Hope Farm), a not-for-profit social organization that works in Brazil and in the world with over 60 centers. Its main goal is to recover substance-addicts based on the treatment tripod of spirituality-relationship-work, without resorting to medications or behavioral therapies. By using this method, it shelters drug-addicts for restructuring their lives transforming them into rehabilitated citizens. Methodology includes both qualitative and quantitative approaches, and the research was carried out through participant observation and questionnaires. The rehabilitee s profile was identified and also the structure and organization of social relations that determine the network at Fazenda da Esperança. Data shows that rehabilitees are, in their majority, young and of similar socio-economic levels. The network analysis, using the proximity and intermediation index, shows that the network is organized around the official leaders on the Fazenda. From the therapeutic tripod in the community, i.e. spirituality-relationship-work, the first has an important role in creating a social bond, as well as in recovering the rehabilitee s values, hence contributing for his consequential reintegration to society